Development of Innovation Project as the Result of Leadership Training Through the Innovation Actor Collaboration Model in the Region - Soesanto, Hari (Jurnal Bina Praja, 2017)
This study is motivated by the change project’s sustainability problem based on the study of PKP2A II LAN (2016) study team, identified after Level IV and Level III Leadership Training (Diklatpim). After the training, there are still some milestones or goals of the projects that have not been achieved. Medium-term and long-term goals have not been assessed because the new Diklatpim only review the general implementation of change projects during the training session. The change projects produced in the process of Diklatpim to achieve short-term goals may have a prospect to be expanded, enabling it to maintain its sustainability and to provide benefits for the region especially in the provision of public services. The current conditions rely solely on the alumni of Diklatpim and their mentors, which makes it somewhat difficult to maintain the sustainability of the change projects effectively. This study aims to provide an alternative policy solution for regional governments to improve the sustainability and increase the scale of the Diklatpim’s change projects. Using literature study methods and qualitative approach, a collaborative model of innovation actors in the regional government for the development of innovation projects is developed. The collaborative model resulting from this study is called the WPPPA Model. This model is a collaboration model between Widyaiswara, Researcher, Planner and Diklatpim Alumni. The successful collaboration process undertaken by key innovation actors will be useful to maintain the sustainability of change projects on a broader scale and increasing the outcome of regional innovation sourced from the change projects.